2016
DOI: 10.1071/he16050
|View full text |Cite
|
Sign up to set email alerts
|

Assessing change in perceived community leadership readiness in the Obesity Prevention and Lifestyle program

Abstract: Issue addressed The context of community-based childhood obesity prevention programs can influence the effects of these intervention programs. Leadership readiness for community mobilisation for childhood obesity prevention is one such contextual factor. This study assessed perceived community leadership readiness (PCLR) at two time points in a state-wide, multisite community-based childhood obesity prevention program. Methods PCLR was assessed across 168 suburbs of 20 intervention communities participating in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
9
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 22 publications
2
9
0
Order By: Relevance
“…Leadership is recognized as important for coordinating and developing community programs and evidence-based program selection. Other studies found that a lack of leadership is associated with unsustainability of implemented programs [44,45]. In line with these studies, the present study found that the availability of leadership is associated with higher levels of the adoption of evidence-based prevention.…”
Section: Discussionsupporting
confidence: 89%
“…Leadership is recognized as important for coordinating and developing community programs and evidence-based program selection. Other studies found that a lack of leadership is associated with unsustainability of implemented programs [44,45]. In line with these studies, the present study found that the availability of leadership is associated with higher levels of the adoption of evidence-based prevention.…”
Section: Discussionsupporting
confidence: 89%
“…We acknowledge the efforts of Kostadinov et al [37, 38] to create an online version of the CRT, currently validated only for the leadership domain. Further research to validate this online forum across all other domains could broaden the reach of the tool and reduce time in interviewing and scoring.…”
Section: Discussionmentioning
confidence: 99%
“…The community capacity domains identified in this review have been suggested to be associated with the success of community interventions by several studies. For instance, the presence of leadership has been recognized as crucial for coordinating and developing community programs and evidence-based program selection [ 90 , 91 ]. Additionally, a sense of community has been identified as an important contextual factor associated with health behavior [ 92 ].…”
Section: Discussionmentioning
confidence: 99%